Changes in prevalence and the cascade of care for type 2 diabetes over ten years (2005-2015): results of two nationally representative surveys in Mozambique - Tavares Madede; Albertino Damasceno; Nuno Lunet; Orvalho Augusto; Carla Silva-Matos; David Beran; Naomi Levitt (BMC, 2022)
Abstract Background Sub-Saharan Africa is predicted to have the steepest increase in the prevalence of diabetes in the next 25 years. The latest Mozambican population-based STEPS survey (STEPS 2005) estimated a 2.9% prevalence of diabetes in the adult population aged 25-64 years. We aimed to assess the change in prevalence, awareness, and management of diabetes in the national STEPS survey from 2014/2015 compared to 2005. Methods We conducted an observational, quantitative, cross-sectional study following the WHO STEPS surveillance methodology in urban and rural settings, targeting the adult population of Mozambique in 2015. We collected sociodemographic data, anthropometric, and 12 hour fasting glucose blood samples in a sample of 1321 adults. The analysis consisted of descriptive measures of the prevalence of impaired fasting glucose (IFG), diabetes and related risk factors by age group, sex, and urban/rural residence and compared the findings to those of the 2005 survey results. Results The prevalence of IFG and diabetes was 4.8% (95CI: 3.6-6.3) and 7.4% (95CI: 5.5-10.0), respectively. These prevalence of IFG and diabetes did not differ significantly between women and men. The prevalence of diabetes in participants classified with overweight/obesity [10.6% (95CI: 7.5-14.6)] and with central obesity (waist hip ratio) [11.0% (95CI: 7.4-16.1)] was almost double the prevalence of their leaner counterparts, [6.3% (95CI, 4.0-9.9)] and [5.2% (95CI: 3.2-8.6)], respectively. Diabetes prevalence increased with age. There were 50% more people with diabetes in urban areas than in rural. Only 10% of people with diabetes were aware of their disease, and only 44% of those taking oral glucose-lowering drugs. The prevalence of IFG over time [2.0% (95CI: 1.1-3.5) vs 4.8% (95CI: 3.6-6.3)] and diabetes [2.9% (95CI: 2.0-4.2) vs 7.4% (95CI: 5.5-10.0)] were more than twofold higher in 2014/2015 than in 2005. However, awareness of disease and being on medication decreased by 3% and by 50%, respectively. Though this was not statistically significant. Conclusions While the prevalence of diabetes in Mozambique has increased from 2005 to 2015, awareness and medication use have declined considerably. There is an urgent need to improve the capacity of primary health care and communities to detect, manage and prevent the occurrence of NCDs and their risk factors.